Effect of Pesticides on Peroxisome Proliferator-Activated Receptors (PPARs) and Their Association with Obesity and Diabetes - J. Hernández-Valdez; A. Velázquez-Zepeda; J. C. Sánchez-Meza (PPAR Research)
Obesity and diabetes mellitus are considered the most important diseases of the XXI century. Recently, many epidemiological studies have linked exposure to pesticides to the development of obesity and type 2 diabetes mellitus. The role of pesticides and their possible influence on the development of these diseases was investigated by examining the relationship between these compounds and one of the major nuclear receptor families controlling lipid and carbohydrate metabolism: the peroxisome proliferator-activated receptors (PPARs), PPARα, PPARβ/δ, and PPARγ; this was possible through in silico, in vitro, and in vivo assays. The present review aims to show the effect of pesticides on PPARs and their contribution to the changes in energy metabolism that enable the development of obesity and type 2 diabetes mellitus.